Choosing the Role of Software in Production and Technology Modeling (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This article provides tips on how to choose model editors for technology modeling, Autodesk Inventor software, and iFeatures, iParts and iMates for model design. The article describes the technology of imitation modeling of the educational process using a three-dimensional modeling tool in teaching computer graphics. Based on this technology, a method, a method, a system of teaching methodologies, tools and methodologies have been developed. In addition, mathematical and statistical analysis of the implementation of this technology in the learning process and the results obtained.